An improved modeling and control approach for DFIG-based wind generation systems - Mohseni, Mansour; Islam, Syed (University of Adelaide, 2009)
A new modeling and control approach for DFIG-based wind generator is presented in this paper. To reduce the modeling complexity, the well-known “T-form” equivalent circuit of induction machine is replaced by the “G-form” circuit. Furthermore, the stator-voltage frame is used for the DFIG vector control, which avoids the need for accurate detection of the stator-flux vector position. A vector-based hysteresis current controller (VBHCC) is then utilized to regulate the current in the rotor side inverter (RSI). In contrast with synchronous PI current regulators, the proposed VBHCC exhibits very fast tracking behavior using a noncomplex control structure. It also considerably reduces the RSI switching frequency by systematic implementation of the zero voltage space vectors. Comprehensive simulation studies are carried out using MATLAB/SIMULINK to investigate the validity of the proposed modeling and control approach.